2008
DOI: 10.1111/j.1365-2109.2008.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Escape-related behaviour of Atlantic cod,Gadus morhuaL., in a simulated farm situation

Abstract: Cultured ¢sh escaping from farms represent an economic loss as well as a potential problem for wild ¢sh populations. This study investigated the escape-related behaviour of farmed Norwegian coastal and northeast Arctic cod (NEAC), Gadus morhua L. Six groups of ¢sh were observed during three replicate trials in a large tank that was split into two equal parts by a net wall. The ¢sh could move freely through an opening in the net during the trials. Three groups were not fed during the trials. The ¢rst escape occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…Previous work has demonstrated that identically farmed adult NCC and NEAC differ with respect to disposition to pass through an opening in a net wall (Hansen et al 2008). Also, Salvanes et al (2004) documented behavioural differences between sub-groups of juvenile cod farmed in common-garden experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has demonstrated that identically farmed adult NCC and NEAC differ with respect to disposition to pass through an opening in a net wall (Hansen et al 2008). Also, Salvanes et al (2004) documented behavioural differences between sub-groups of juvenile cod farmed in common-garden experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, genetic and other factors like hunger level, stocking density and environmental variation might affect the escape likelihood of cod. It has, for example, been shown that the 2 genotypes Norwegian coastal cod (NCC) and north-east Arctic cod (NEAC) exhibit a movement pattern within rearing tanks that might involve higher escape risk (Hansen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Atlantic cod, Gadus morhua, escaping from net cages revealed consistent individual differences between the fish escaping compared with nonescaping fish, with bold individuals being more willing to swim through small holes in the net, and thus escape more frequently than shy fish (Hansen et al 2008). These responses are generally linked with the learning ability of farmed fish.…”
Section: The Diversity Of Behavioural Responses and Coping Stylesmentioning
confidence: 99%
“…Given that farmed cod spawn in the cages, embryos with cultivated cod genes drift out of sea cages into the environment, escaping through spawning (Jørstad et al 2008, Jensen et al 2010). If they survive, they may interact with wild cod with possible negative implications, including competition for food and other resources, mating competition, and outbreeding depression (Hansen et al 2008). If the fish have been intensely selected for domestication, they can introduce domestic adaptations that disrupt local adaptations of wild cod (Hindar et al 1991).…”
Section: Introductionmentioning
confidence: 99%